Quantitative and qualitative electroencephalography in the diagnosis and monitoring of depression. A modern approach to clinical neurophysiology - Kopańska, Marta; Ochojska, Danuta; Sarzyńska, Izabela; Bartkowska, Oliwia; Szczygielski, Jacek (Frontiers in Human Neuroscience, 2025)
ContextDepressive disorders are one of the greatest public health challenges, affecting more than 300 million people worldwide. Traditional diagnostic methods are based on subjective clinical assessments, which limits their accuracy and reproducibility. Therefore, there is an urgent need to implement objective, easily accessible diagnostic tools. One such tool is quantitative electroencephalography (QEEG), which allows for the analysis of the bioelectrical activity of the brain in a non-invasive and precise manner.MethodsIn this narrative review, the latest research on the use of QEEG and traditional EEG in the assessment of patients with major depressive disorder (MDD) was analyzed. The literature search was carried out in the PubMed and SpringerLink databases, focusing on articles investigating the correlations between spectral EEG properties (alpha, beta, theta, delta, gamma waves) and symptoms of depression.ResultsThe literature review indicates the presence of characteristic patterns of brain activity in patients with MDD, such as alpha wave asymmetry in the frontal areas, increased beta band activity, and changes in the theta and delta waves. This indicates the potential use of these parameters as biomarkers for early detection and monitoring of therapy effectiveness.ConclusionsQEEG and classical EEG may play an important role in the diagnosis and treatment of depression, supporting the development of personalized therapeutic strategies. Despite promising results, further research on the standardization of methods and validation of neurophysiological indicators is needed to enable their wider application in psychiatric clinical practice.